Effect of herbal extract on rat bone marrow stromal derived osteoblast growth and differentiation in vitro / Poon Chi Tat - Poon, Chi Tat (2013)
Drynaria quercifolia (D.quercifolia) and Justicia gendarussa (J.gendarussa) are locally found herbs. Proper scientific studies were initiated to test the effects of the two plants and a pre-mixed herbal formulation (Bo-Gu-Cao formulation) with J.gendarussa as the main constituent. Rat bone marrow derived osteoblasts (rBMS-derived osteoblasts) were used as research subject in the present study. The effects of the herbal extracts on the cells were evaluated by comparing cell number and alkaline phosphatase (ALP) activity of the tested cells to control. Samples of D.quercifolia, J.gendarussa, and pre-mixed Bo-Gu-Cao formulation were dried, powdered, and extracted with solvents of different polarities. Herbal extracts were reconstituted in media (at a concentration of 100 μg/ml) and subjected to proliferation rate, ALP activity evaluation, and staining of calcium deposition. Bone marrow stromal cells were isolated from tibias and femora of Sprague Dawley rats and subsequently induced to osteogenic differentiation. The cells were identified as bone marrow stromal cells prior to osteogenic differentiation by standard stem cell characterization. Cells were incubated with herbal extracts and evaluated with proliferation rate and ALP activity. Statistical analysis was performed by using One-Way ANOVA test to compare the means of samples and control values. A total of 12 herbal extracts were obtained from the two herbs and the pre-mixed herbal formulation. Bone marrow stromal cells were identified as the microscopic observation confirmed attachment to plastic surface and fibroblastic morphology, characterized by CD90+, CD45- and CD31-, and the cells were able to be induced to osteoblasts, chondrocytes, and adipocytes. Calcium deposition by rBMS derived osteoblasts was stained by Alizarin Red S staining.Water extract of D.quercifolia and water extract of J.gendarussa and Bo-Gu-Cao formulation consistently induced a significant enhancement on rBMS derived osteoblast proliferation on day 7 and day 14 of incubation. ALP activity was enhanced significantly in the cells incubated with water extract of D.quercifolia and J.gendarussa for 7 days and 21 days. The dose dependency effect evaluation had shown the optimum dosage for D.quercifolia water extract, while there is no dose dependency effect found on water extract of J.gendarussa. The results of the present study reveals that the medicinal herbs used in this study possess certain substance/s that can enhance osteoblast proliferation as well as differentiation and can be postulated in aiding bone healing. It can be concluded that water extract of D.quercifolia and J.gendarussa are the potential herbal extracts to be further investigated. Isolation of active compounds from D.quercifolia and J.gendarussa are to be done and effects of the active compounds on osteoblasts are to be evaluated.